The Tudor Domain-Containing Protein, Kotsubu (CG9925), Localizes to the Nuage and Functions in piRNA Biogenesis in D. melanogaster - Lim, Lin-Xenia; Isshiki, Wakana; Iki, Taichiro; Kawaguchi, Shinichi; Kai, Toshie (Frontiers in Molecular Biosciences, 2022)
Silencing of transposable elements (TEs) by Piwi-interacting RNAs (piRNAs) is crucial for maintaining germline genome integrity and fertility in animals. To repress TEs, PIWI-clade Argonaute proteins cooperate with Tudor domain-containing proteins at membraneless perinuclear organelles, called nuage, producing piRNAs to repress transposons. Here, we identify and characterize one of the Drosophila Tdrd1 orthologues, Kotsubu (Kots), which is a Tudor domain-containing protein encoded by CG9925 whose protein localizes to the nuage in gonads. We further show the dynamic localization of Kots in the male germline, where it shows perinuclear signals in spermatogonia but forms large cytoplasmic condensates in the spermatocytes that overlap with piNG-body components, a nuage-associated organelle. The loss of kots resulted in a notable upregulation of stellate and a corresponding reduction in the Suppressor of Stellate piRNAs in the mutants. Furthermore, a moderate yet significant reduction of other piRNAs was observed in kots mutant testes, albeit to a weaker extent in mutant ovaries. Taken together, we propose that Kots functions in the piRNA pathway, predominantly in the male germline by forming discrete cytoplasmic granules.